From silence to sound : Beethoven's beginnings - Yudkin, Jeremy (Boydell Press, 2020)
This book discusses the myriad ways in which Beethoven begins his works and the structural, rhetorical, and emotional implications of these beginnings for listeners. Examining the opening moments of nearly 200 compositions, it offers a new method of analysis of Beethoven's music. At the same time, it sets Beethoven's work in context through a close study of beginnings in the compositions of the Classical Era.